Evaluation of KIM-1 as an early biomarker of snakebite-induced AKI in mice. (1st September 2018) - Dantas, Rodrigo Tavares; Sampaio, Tiago Lima; Lima, Dânya Bandeira; Menezes, Ramon Róseo Paula Pessoa Bezerra de; Canuto, Jader Almeida; Toyama, Marcos Hikari; Evangelista, Janaína Serra Azul Monteiro; Martins, Alice Maria Costa
Abstract: Acute kidney injury (AKI) is one of the most important complications of bothropic poisoning and its early identification remains challenging. The nephrotoxicity of Bothrops insularis venom (BinsV) was previously described by our research group. In this study, we continued to evaluate the effect of BinsV on kidney function in mice and LLC-MK2 proximal tubule cells, evaluating KIM-1 protein as an early AKI biomarker. Male Swiss mice were inoculated with BinsV intramuscularly and observed for 24 h in a metabolic cage model. Urine and blood were collected for biochemical analyses and the kidneys were examined for oxide-reducing balance and submitted to histological analysis. LLC-MK2 cells incubated with BinsV were assessed for cell viability and cell death mechanism by flow cytometry. Histological analysis of the kidneys indicated AKI and the oxide-reducing analyses demonstrated a decreasing in reduced glutathione (GSH) levels and an increasing on Malondialdehyde (MDA) levels. BinsV was cytotoxic to LLC-MK2 and the cytometry analyses suggested necrosis. Within 24 h after the envenomation, urinary creatinine did not increase, but the urinary levels of KIM-1 increased. In conclusion, we found AKI evidence in the kidney tissue and the increase in the KIM-1 levels suggest it can be used as an early AKI biomarker. Highlights: Bothrops insularis venom (BinsV) is nephrotoxic. BinsV induces Acute Kidney Injury in mice. Discrepancies were observed between plasmatic creatinine and histological findings. Urinary KIM-1 was increased in mice inoculated with BinsV after 24 h. Urinary KIM-1 was suggested as specific and early AKI biomarker on envenomation.